Analisis Pengaruh Mobilitas Penduduk terhadap Kasus Covid-19 Selama Masa Pandemi di Indonesia Menggunakan Regresi Linier Berganda - Dining Dwi Suci Riyani; Malecita Nur Atala Singgih; Zumrotul Wahidah; Edy Widodo (Jurnal Teknologi, Fakultas Teknologi Industri, Institut Sains & Teknologi AKPRIND Yogyakarta, 2021)
Mobility of population is closely related and is thought to have an effect on the number of COVID-19 cases. From time to time, the movement of people's mobility is mapped geographically in various categories, namely retail and recreation, grocery stores and pharmacies, parks, public transportation centers, workplaces, and residential areas. Population mobility is very closely related and is thought to have an effect on the number of Covid-19 cases, population movements greatly affect the social interaction of the population itself, the more activities residents carry out, the more interactions are created and can cause the spread of the virus chain to increase. Therefore, population mobility can be used as a means for the government to take more efficient policies in solving the problems of the COVID-19 pandemic. This research uses the Multiple Regression method which aims to find out what categories of factors affect Covid-19 cases in Indonesia during the pandemic. The results found that the mobility category of residential areas, parks, and public transportation had a significant effect on Covid-19 cases in Indonesia during the pandemic.